Developing dementia: The existential experience of the quality of life with young-onset dementia – A longitudinal case study. (April 2020) - Thorsen, Kirsten; Dourado, Marcia Cristina Nascimento; Johannessen, Aud
Background: Cognition and the ability to take care of daily activities and oneself gradually declines among people with dementia. Studies are scarce, especially regarding how people with young-onset dementia (YOD) (<65 years) experience the quality of their lives with the progression of dementia. People with dementia living alone face special challenges. Aim: To examine the experience of the quality of life with YOD as a single person. Method: The study presents a longitudinal case study with in-depth interviews exploring the experiences of a person with YOD. Individual interviews were conducted seven times over a period of three years from 2014 to 2017. Findings: We examined if and how seven themes concerning the quality of life and well-being were fruitful for understanding the experiences of dementia in the everyday life of a single individual. The study explored needs and challenges during the development of dementia, and how the person reacted over time, set in context. The themes significant for well-being are: identity, connectedness, security, autonomy, meaning, growth and joy. Conclusion: The study shows how treatment, support, and services must be individualized when dementia develops in order to support identity, resources and mastering capacity, and promote well-being.